ANALISIS MODEL KEPUASAN KONSUMEN BERDASARKAN PENGARUH KEUNIKAN NAMA USAHA DAN NILAI KULINER - Setiawan, Andi (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2012)
This article is a research for researchers in marketing, particularly brand. This article isformulated based on the record and the facts that are found in the field. Facts where industriaculinary competition at this time spawned creativity in finding a name that has a unique culinaryefforts. uniqueness is on one side in an effort to build differentiation to competitors and at thesame time aim to influence customer satisfaction. This article attempts to explore further thefactors that lead to a better culinary value and how the value of culinary and business name to bedeterminants of consumer satisfaction. Formulation variables and indicators refer to previousresearch studies. A model has been developed and three hypotheses have been formulated toaddress the research problem. The sampling technique is quota sampling. Respondents of thisresearch were 100 respondents, of which the respondent is a consumer culinary Semarang. Dataanalysis tool used is Structural Equation Modelling (SEM) in AMOS 16.0 program. The resultsof the data analysis of this study suggests a third model and research hypothesis can be accepted.Managerial Implications give advice to focus on the influence of culinary value to customersatisfaction culinary in Semarang.